Properties of acyl modified poly(glycerol-adipate) comb-like polymers and their self-assembly into nanoparticles - Taresco, Vincenzo; Suksiriworapong, Jiraphong; Creasey, Rhiannon; Burley, Jonathan C.; Mantovani, Giuseppe; Alexander, Cameron; Garnett, Martin (Wiley, 2016)
There is an increasing need to develop bio-compatible polymers with an increased range of different physicochemical properties. Poly(glycerol-adipate) (PGA) is a biocompatible, biodegradable amphiphilic polyester routinely produced from divinyl adipate and unprotected glycerol by an enzymatic route, bearing a hydroxyl group that can be further functionalized. Polymers with an average Mn of ∼13 kDa can be synthesized without any post-polymerization deprotection reactions. Acylated polymers with fatty acid chain length of C4, C8, and C18 (PGAB, PGAO, and PGAS, respectively) at different degrees of substitution were prepared. These modifications yield comb-like polymers that modulate the amphiphilic characteristics of PGA. This novel class of biocompatible polymers has been characterized through various techniques such as FT-IR, 1H NMR, surface, thermal analysis, and their ability to self-assemble into colloidal structures was evaluated by using DLS. The highly tunable properties of PGA reported herein demonstrate a biodegradable polymer platform, ideal for engineering solid dispersions, nanoemulsions, or nanoparticles for healthcare applications.